Henry James’s Characters: Ethics through Different Awarenesses - Abbate, Fabrizia (Filosofia Morale/Moral Philosophy, 2024)
In this contribution we propose an ethical reading of some of Henry James’ characters, focusing in particular on The Portrait of a Lady, one of the masterpieces of world literature, a milestone in the social and psychological debate related to women’s awareness and emancipation. Relying on the dialectical tools of hermeneutics, we analyze the meanings of moral actions and feelings as built into the plot, comparing different paths of ethical awareness.